2021
DOI: 10.1021/jacs.1c08281
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-Sized Single Crystal of a One-Dimensional Lead-Free Mixed-Cation Perovskite Ferroelectric for Highly Polarization Sensitive Photodetection

Abstract: Linear dichroic anisotropic photonic materials are highly attractive due to their great potentials in many applications, which in combination with the ferroelectric properties could broaden their research and applications. However, to date, the linear dichroism conversion phenomenon has not been observed in one-dimensional (1D) large-size single-crystal materials: in particular, lead-free perovskite ferroelectric crystals. Here, we propose a new ferroelectric design strategy: namely, partial organic cation sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Low-dimensional structures, especially one-dimensional (1D) and two-dimensional (2D) structures, are also anisotropic atomic structures that could produce interesting anisotropies, such as anisotropic electronic structure, anisotropic carrier transport, and birefringence. Recently, examples of low-dimensional perovskite materials have shown linear dichroism behaviors and outstanding anisotropic properties and exhibited more promising applications in polarized luminescence, polarized photon detection, and optical modulation. As is known, the large single crystals have a minimal number of grain boundaries and fewer structural defects and therefore usually lead to enhanced performance. , Several 2D hybrid perovskite single crystals have been synthesized recently, showing excellent anisotropic photonic performance. , Recently, Zhang et al reported centimeter-sized 1D perovskite ( n -propylammonium)­(methylammonium)­SbBr 5 single crystals with excellent linear dichroic anisotropy . However, reports of large 1D perovskite single crystals have been limited, and the corresponding anisotropic property has therefore also not been demonstrated.…”
mentioning
confidence: 99%
“…Low-dimensional structures, especially one-dimensional (1D) and two-dimensional (2D) structures, are also anisotropic atomic structures that could produce interesting anisotropies, such as anisotropic electronic structure, anisotropic carrier transport, and birefringence. Recently, examples of low-dimensional perovskite materials have shown linear dichroism behaviors and outstanding anisotropic properties and exhibited more promising applications in polarized luminescence, polarized photon detection, and optical modulation. As is known, the large single crystals have a minimal number of grain boundaries and fewer structural defects and therefore usually lead to enhanced performance. , Several 2D hybrid perovskite single crystals have been synthesized recently, showing excellent anisotropic photonic performance. , Recently, Zhang et al reported centimeter-sized 1D perovskite ( n -propylammonium)­(methylammonium)­SbBr 5 single crystals with excellent linear dichroic anisotropy . However, reports of large 1D perovskite single crystals have been limited, and the corresponding anisotropic property has therefore also not been demonstrated.…”
mentioning
confidence: 99%
“…Then, a 1D lead-free perovskite ferroelectrics have been discovered by Zhang et al for linearly polarized light photodetection with a large polarization ratio of 6.9. [197] Table 1. Reported polarization-sensitive photodetectors based on anisotropic systems and their critical performance parameters (Abbreviations: PCAR, photoconductance anisotropy ratio; PR, photocurrent ratio; OAR, optical absorbance ratio; PAR, photocurrent anisotropy ratio).…”
Section: D Materialsmentioning
confidence: 99%
“…[92] The light-emitting properties can be flexibly tuned by the management of the energy-level alignment between the organic and organic components. When the exciton level of the inorganic layer is located above the singlet level of organic spacers, the luminescence of 2D perovskites is mainly dominated by the OC [108,109] PV [110,111] MG [112] FE [113,114] CO [115] PZE [116] 1D -LM [17,117] FE [118,119] FM [120] 0D [121,122] PV [123] FE [124] a) E g (bandgap), e (electronic effective mass), m h (hole effective mass), E b (exciton binding energy), optoelectronic (OC), photovoltaic (PV), magnetic (MG), ferroelectric (FE), chiral optics (CO), piezoelectricity (PZE), luminescence (LM), ferromagnetism (FM). The E b is assessed by using a simple Wannier exciton model.…”
Section: Excitonic Characteristic and Luminescence Mechanism Of Ldpsmentioning
confidence: 99%